QUARTERLY VARIATION OF TROPOSPHERIC SURFACE REFRACTIVITY IN ILORIN, NIGERIA - Otto, Muhammed Sani; Oladiran, Abimbola Johnson; Oluwasesan, Falaiye Adeniran; Muhammad, Faisal Usman; A.A Sule (Malaysian Journal of Science, 2023)
To construct a radio communication system, there is need for extensive knowledge of the refractivity and its variations. This work aims to determine the change in season with tropospheric surface refractivity of Ilorin, Kwara, Nigeria. The refractivity for both dry (1st quarter) and rainy (3rd quarter) seasons for 2000 - 2002 have been calculated using the meteorological data obtained from the Nigerian Meteorological Agency, Ilorin. The result shows that there is a variation between tropospheric surface refractivity during the dry and rainy seasons. High refractivity during the rainy season than in dry season is observed, mainly due to higher amount of water content in the atmosphere (troposphere) in the rainy season.